Mediterranean diet and its impact on the prevention of depressive disorder (Research, Society and Development, 2023)
Objective. To assess the relationship between the Mediterranean diet and the prevention of depressive symptoms. Methods. A integrative review was conducted, assessing articles published in the last 10 years, using PubMed, Scielo, BMC Nutrition and MDPI databases. The keywords used in this study were “mediterranean diet and depression”. Results. Nine articles were selected, eight of them established a relation between the Mediterranean diet and the prevention of depressive symptoms, while one did not demonstrate this association. Conclusion. The Mediterranean diet provides polyunsaturated fatty acids (omega 3), B-complex vitamins, vitamin D, C and E, zinc, magnesium and essential amino acids. Furthermore, it contributes to anti-inflammatory action within the body, with these components playing a significant role in mental health. Nevertheless, further observational studies are required to corroborate the findings of this review.